Processes and ore deposits of ultramafic-mafic magmas through space and time - Sisir K.Mondal (Elsevier, 2018)
Processes and Ore Deposits of Ultramafic-Mafic Magmas through Space and Time focuses on the fundamental processes that control the formation of ore deposits from ultramafic-mafic magmas, covering chromite, platinum-group element (PGE), Ni-sulfides and Ti-V-bearing magnetite. The exploration, exploitation and use of these magmatic ores are important aspects of geology and directly linked to the global economy. Magmatic ores form from ultramafic-mafic magmas and crystallize at high-temperature after emplacement into crustal magma chambers, and are genetically linked to the evolution of the parental magmas through space and time. This book features recent developments in the field of magmatic ore deposits, and is an essential resource for both industry professionals and those in academia.Elucidates the relationships between tectonic settings and magmatic ore mineralizationProvides the links between magma generation in the mantle and ore mineralization at crustal levelsFeatures the latest research on changing patterns in magmatic ore mineralization through time and their bearing on the chemical evolution of the Earth's mantle--